On Metaphysics and the Political: A Polemics of Reading Baudelaire in the 1930s. Issue 2 (July 2019) - Acquisto, Joseph
Abstract : This essay examines a polemic between two Baudelaire critics of the 1930s, Jean Cassou and Benjamin Fondane, which centered on the relationship of poetry to progressive politics and metaphysics. I argue that a return to Baudelaire's poetry can yield insight into what seems like an impasse in Cassou and Fondane. Baudelaire provides the possibility of realigning metaphysics and politics so that poetry has the potential to become the space in which we can begin to think the two of them together, as opposed to seeing them in unresolvable tension. Or rather, the tension that Baudelaire animates between the two allows us a new way of thinking about the role of esthetics in moments of political crisis. We can in some ways see Baudelaire as responding, avant la lettre, to two of his early twentieth-century readers who correctly perceived his work as the space that breathes a new urgency into the questions of how modern poetry relates to the world from which it springs and in which it intervenes.